Interventional, Quasi-Experimental Study of a Chronic Obstructive Pulmonary Disease Education Care Plan for Hospital Discharge - Letitia N. Warunek; Nicole E. Cieri-Hutcherson; Brian P. Kersten; Amany K. Hassan (MDPI AG, 2021)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity, mortality, and reduced quality of life for patients. Proper use of inhaler devices is critical for effective drug delivery and prevention of COPD progression. The primary endpoint of this study was a mean percent increase in correct steps associated with inhaler technique after pharmacist education. The co-primary endpoint was a 25% increase in the proportion of patients correctly identifying the appropriate use of short-acting versus long-acting inhaler types. This was an interventional quasi-experimental study of patients hospitalized at a 491-bed tertiary academic medical center with a COPD exacerbation to assess a pharmacist-led COPD care plan. Eligible patients included general floor, adult patients admitted with a primary diagnosis of COPD exacerbation. The primary investigator recorded initial inhaler technique scores through a paper checklist, and provided education about device types and usage. Patients were reassessed within 48 h to determine if pharmacist education improved inhaler knowledge. A total of 67 patients received the COPD care plan before hospital discharge. At baseline, patients scored a median of 81.8% (67.5-97.0) of steps correct across all inhaler device types. After pharmacist education, patient scores increased to a median of 100% (90.9-100.0) (p < 0.0001). The proportion of patients correctly identifying when to use short-acting versus long-acting inhalers increased from 73.1% to 98.5% (p < 0.0001). Implementation of a pharmacist-led care plan for patients admitted for COPD exacerbation was associated with an increase in correct steps for appropriate inhaler technique and understanding of inhaler device types after pharmacist education.